The Scarpetta Factor - Cornwell, Patricia (United States : Sphere, 2009)
Kay Scarpetta--now a senior forensic analyst for CNN--becomes embroiled in a surreal plot that includes a famous actor accused of an unthinkable sex crime and the disappearance of a beautiful millionairess with whom her niece Lucy seems to have shared a secret past.
Keywords: Medical examiners (Law); Forensic pathologists; Women physicians